2022
DOI: 10.3390/jcm11185281
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Is Beneficial to Gut Microbiota Homeostasis during Colonoscopy: Randomized Controlled Trial

Abstract: Background: Many studies have reported minor complications and disturbance of the gut microbiota after colonoscopy. Compared with air, carbon dioxide (CO2) insufflation could decrease minor complications, but its impact on gut microbiota remains unknown. Methods: Thirty-eight healthy subjects were assessed and twenty were randomized to receive either CO2 or air insufflation during colonoscopy. Neither the participants nor the staff involved in the follow-up knew which gas was used. Minor complications were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…We also identified a decreased abundance of B. caccae in association with Pb exposure in the second trimester using TWAS, and B. caccae was also heavily weighted in WQS RSRH for both trimesters of prenatal Pb exposure. B. caccae are common fiber degraders in the human gut microbiome, with mixed health effects (Wexler, 2007;Chen et al, 2021;Yang et al, 2022;Zhang et al, 2022). This consistent association of prenatal Pb exposure and decreased B. caccae abundance both early and late in childhood, from different populations in different countries, is strong evidence of association in this relatively new field.…”
Section: Discussionmentioning
confidence: 72%
“…We also identified a decreased abundance of B. caccae in association with Pb exposure in the second trimester using TWAS, and B. caccae was also heavily weighted in WQS RSRH for both trimesters of prenatal Pb exposure. B. caccae are common fiber degraders in the human gut microbiome, with mixed health effects (Wexler, 2007;Chen et al, 2021;Yang et al, 2022;Zhang et al, 2022). This consistent association of prenatal Pb exposure and decreased B. caccae abundance both early and late in childhood, from different populations in different countries, is strong evidence of association in this relatively new field.…”
Section: Discussionmentioning
confidence: 72%
“…The reason for the different relapse rates between groups at week 8 but not at week 1 is unclear; nevertheless, changes in the intestinal microbiota of the patients may provide a partial explanation. A recent RCT that examined changes in gut microbiota in fecal samples collected after colonoscopy with CO 2 or air insufflation reported that the relative abundance of some Bacteroides members, which were all obligate anaerobes, was significantly higher in the CO 2 insufflation group than in the air insufflation group [ 20 ]. Furthermore, previous studies reported that a decrease in normal anaerobic bacteria, including Bacteroides , Eubacterium , and Lactobacillus species, is associated with the pathogenesis of mucosal inflammation in patients with IBD [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%